Lead-dependent infective endocarditis in a patient with five old pacemaker leads – less invasive management - Kutarski, Andrzej; Oleszczak, Krzysztof; Młynarczyk, Krzysztof; Czajkowski, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Recently, the indications for surgical treatment of patients with an infected pacing system were clearly defined in guidelines, but the rules are not always followed in everyday practice and still too many patients are treated with open chest surgery. The described case shows that even severe cases of systemic infection with old, strongly imbedded multiple leads, even when located in the cardiac vein system, can be treated with transvenous lead extraction (TLE).